Mental Criticism of Models from the Biography of Ibn Hisham ( the Third Part ) - Abdullah , Zahraa (Islamic Sciences Journal, 2023)
The research included an introduction, four investigations, and a conclusion: In the introduction, I explained the reasons that prompted me to choose the topic. As for the first topic, it defines and originates criticism, and it includes three demands: The first requirement: the definition of criticism in language and convention, the second requirement: the legitimacy of criticism, and the third requirement: the origins of modern criticism. As for the second topic: it contains the causes and methods of criticism, and it included three demands, the first: in the direct causes of criticism of the hadith, the second: in the approach of the modernists in explaining the hadiths, and the third in the party of criticism of the hadith. As for the third topic: In the Biography of the Prophet, the causes and method of the modernizers criticize its news and has two requirements: The first: the reasons for criticizing and correcting the biography news, and the second: Approach of the modernists in the criticism of telling the biography of the Prophet. As for the fourth topic: the last one, it includes: Examples of criticism in the news of the biography and it contains four demands: The first requirement: on the marriage of the Messenger (may Allah’s prayers and peace be upon him) to Maymouna bint Al-Harith while he is, and the second requirement: in the news of breaking from the hadith of Aisha (may Allah be pleased with her) ) In the biography of Ibn Hisham, and the third requirement: In the killing of Hamzah bin Abdul Muttalib, the master of the martyrs and the uncle of the Messenger of Allah (may God bless him and grant him peace), and the fourth requirement: In the lament of Saad bin Muadh (may Allah be pleased with him).